Клінічний випадок альдостероми - Підмурняк, О. О.; Мукомела, Л. І. (Clinical Endocrinology and Endocrine Surgery, 2010)
This article describes a case of early diagnostics of adrenal tumor — aldosteroma which caused arterial hypertension. After diagnostics the laparoscopic adrenalectomy was performed. Histological findings — clear cell adenoma of cortex with low mitotic activity. No postoperative complication was found. Received experience gave us opportunity to claim that contemporary medicine gives a possibility of early clinicaboratory and tool diagnostics arterial hypertension caused endocrine disorders. Modern technology like laparoscopic adrenalectomy gave us opportunity to reach a desirable result quick and safety.